Features of video-pulse parameters simulation for studying spectra of secondary electromagnetic radiation - Zabolotny, V.I.; Perepadia, V.I. (Radiotekhnika, 2018)
Features of video-pulse parameters simulation for studying spectra of secondary electromagnetic radiation are described on the basis of the Monte-Carlo statistical test method. It is established that the key parameters in terms of the possibility of information leakage are: the length of the smooth transition of the signal between the linear parts and the length of the approximation of the linear component of the pulse front, which determine the shape of the signal. Using a probabilistic approach, a method for determining the density distribution of the probability of electric field intensity at the boundary of the controled zone is described to assess the technical protection of information.